Current issues in English language education in the Kingdom of Saudi Arabia - Al-Hazmi, Sultan (Journal of Modern Languages, 2017)
There has been a considerable debate about English education programs in Saudi schools and colleges in recent years. The role of educational institutions in preparing students for the world of work, much of it in English, has come to be recognized. The introduction of English as a subject in the elementary stage of the Saudi school system in 2004/5 is another sign of its growing importance. Perception of the need for English, however, has not always been matched by satisfactory educational outcomes. Currently there is an ongoing nationwide debate about the low proficiency level in English among secondary school graduates. the inadequate number of well-trained teachers of English, and inappropriate materials and pedagogy. This paper revisits these concerns with a view to providing insights for the improvement of English education programs in The Kingdom of Saudi Arabia that policy makers, administrators and educators constantly seek.